Knowledge about prevention and risk factors for cervical cancer in a technical education center - Narváez Ocampo, Leidy Johana (2019)
Introduction: Cervical cancer is a public health problem. Objective: To determine the level of knowledge about prevention and risk factors for cervical cancer in women of a technical institute in the city of Cali, Colombia. Methods: Cross-sectional study with the participation of 131 women enrolled in any of the academic programs of the educational institution, to whom a structured survey was applied. Results: The general average of positive answers was 51.7%. The correct knowledge on prevention was calculated in 86.1%, while the knowledge of risk factors was estimated in 34.6%. Conclusions: We found a high level of knowledge regarding cytology and the vaccine against human papillomavirus in questions of preventive methods, but the knowledge on risk factors for the development of cervical cancer was low. These deficiencies could be related to low socioeconomic and academic levels in the population studied.